Contextualising narrative inquiry : developing methodological approaches for local contexts - Trahar, Sheila (Routledge, 2013)
"Narrative inquiry is growing in popularity as a research methodology in the social sciences, medicine and the humanities. In narrative inquiry, the transparency of interactions between researcher and research participants, together with rich, contextual descriptions, help to shape and structure research texts rendering them engaging and readable. Contextualising Narrative Inquiry argues that all researchers should foreground the importance of the context in which research takes place and develop methodological approaches that are grounded in their local contexts. To do so, they need to pay attention to how knowledge is constructed, shared and understood in those contexts. This is particularly important when contexts have been subjugated historically through colonialism and when local, Indigenous ways of knowing have been ignored or dismissed"--EBL.